Phonebooth - Schumacher, Joel (Pasig City : Viva Video, 2002)
" PICK UP THIS THRILLER THAT NEVER LET'S YOU GO!" Stu Shepart (Colin Farrell) is an arrogant publicist lying this way to success in New York. Everything changes however when he unknowingly answers a call in a phone booth he's been using to cheat on his wife. Now he is at the mercy of the caller (Kiefer Sutherland who, as an invisible sniper somewhere in the buildings above, is holding him hostage with demands to come clean with his wife (Radha Mitchel) and his girlfriend (Katie Holmes). Relying on his wits and the unlikely help of Capt. Ramsey (Forest Whitakers) Stu's life will change even if he does manage to escape alive. This highly original suspense thriller from director Joel Schumacher (Batman Forever, 8MM, Falling Down) is filled with action and unbelievable moments when all of new york comes to a standstill for one harrowing conclusion.